Clays and Clay Minerals, Vol. 58, No. 5, 596–605, 2010. - Kuehn, Thomas; Poellmann, Herbert (The Clay Minerals Society, 2010)
Layered double hydroxides (LDHs) are layered ion exchangers, with a large surface-charge density, which react easily with organic anions. Various types of organics are rapidly substituted in the interlayer space of inorganic precursor LDHs. ZnAl-LDHs were intercalated with 1- to 19-carbon monocarboxylic acid anions by anion exchange of NO3 --saturated LDH precursor phases in order to study the dependence of exchange reactions on synthesis parameters (temperature, pH, and interlayer anion). The carboxylic acid anion-LDHs synthesized were characterized using X-ray diffraction, infrared spectroscopy, thermal analysis, scanning electron microscopy, chemical analysis, and N2 adsorption. Carboxylic anion quantities in excess of the LDH anion exchange capacity easily replaced exchangeable nitrate anions at moderate pH. The intercalated LDH interlayer space depended on the alkyl chain length and orientation (inclination angle) of thecarboxylic-ac id anion. Thelatticeparame ter c0 ranged from 3.4 to 13.5 nm, but the a0 lattice parameter remained constant at 0.31 nm. Crystallographic analyses indicated a monomolecular arrangement of intercalated short-chain fatty-acid anions. At pH < 7, intercalated longchain carboxylates showed a preferred bimolecular interlayer orientation. Carboxylic-acid anion exchange with LDHs at pH 7 resulted in the formation of two different sets of basal spacings, which indicated the coexistence of LDHs intercalated with monomolecular and bimolecular arrangements of interlayer carboxylic compounds. Thermal treatment of the carboxylic acid anion-intercalated LDHs indicated stability up to ~140ºC. The release of interlayer water led to distortion of the crystallographic units and resulted in smaller basal spacings without collapse of the layered structure. Heat treatment re-oriented alkyl-chain carbon carboxylates (with >10 carbons) to a more upright interlayer position.
Synthesis And Characterization Of Zn-al Layered Double Hydroxides Intercalated With 1- To 19-carbon Carboxylic Acid Anions
gsccm58502-kue.pdf -- 524KB
Keywords: Periodicals; Geology; Anion Exchange; Carboxylic Acid Anion; Hydrotalcite; LDH